Peningkatan Hasil Belajar IPA Peserta Didik SMP Negeri 1 Kutasari melalui Penerapan Model Problem Based Learning - Desinta Dwi Nuriyanti; Abdul Haris; Asmawati Asmawati (Celebes Science Education, 2022)
This Classroom Action Research aimed to improve student learning outcomes in the eighth grade at SMP Negeri 1 Kutasari on the Excretory System topic through the implementation of a Problem-Based Learning model using plasticine and video media. The subjects of this study were 15 eighth-grade students in class 8B. The research was conducted in three cycles. Student learning outcomes data were collected through Google Forms-based assessments. The collected data were then analyzed using descriptive statistical analysis. The average learning outcomes score in Cycle I was 42.67. In Cycle I, plasticine was used to reconstruct a nephron model. In Cycle II, the average score increased to 67.31, indicating an improvement in learning outcomes compared to Cycle I. Further improvement occurred in Cycle III, with the average learning outcome score reaching 91.67. Classical completeness (percentage of students achieving a minimum passing score of 70) in Cycle I was 20%, in Cycle II it was 46.67%, and in Cycle III it reached 100%. The research findings indicate that the PBL model can improve science learning outcomes for eighth-grade students at SMPN 1 Kutasari.